2000
DOI: 10.1128/jvi.74.2.1004-1007.2000
|View full text |Cite
|
Sign up to set email alerts
|

A Human Milk Factor Susceptible to Cathepsin D Inhibitors Enhances Human Immunodeficiency Virus Type 1 Infectivity and Allows Virus Entry into a Mammary Epithelial Cell Line

Abstract: The cell source of prolonged production of human immunodeficiency virus type 1 (HIV-1) in breast milk (8, 11, 21-23, 26, 27, 29) is not yet clear, since lymphocyte counts in milk decline rapidly after delivery (15). The risk of mother-to-child transmission through breast-feeding has been reemphasized recently, when discontinuation of antiretroviral therapy was followed by an increase in HIV-1 RNA load (10, 13). Therapy withdrawal in a mother after childbirth might also increase viral load in milk, although a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…The 2-fold dilution of human milk demonstrated a significant degree of viral inhibition (>90%; P < 0.05) in comparison with the PBS control ( Figure 1A), which corresponds with previous reports (44)(45)(46)(47)(48)(49). We also identify an enhancement to infection at the 1:10 dilution similar to findings from a previous study (38). Preincubation of the same human milk sample (1:2) with HIV-1 before addition to CD4 + T lymphocytes ( Figure 1B) showed no inhibitory effect in comparison to the PBS control, indicating that the inhibition shown in Figure 1A is not due to a direct virucidal effect of the milk and that the effect is likely conferred on the CD4 + lymphocyte.…”
Section: The Effect Of Human Milk On Direct Hiv-1 Infection Of Cd4 + supporting
confidence: 81%
See 1 more Smart Citation
“…The 2-fold dilution of human milk demonstrated a significant degree of viral inhibition (>90%; P < 0.05) in comparison with the PBS control ( Figure 1A), which corresponds with previous reports (44)(45)(46)(47)(48)(49). We also identify an enhancement to infection at the 1:10 dilution similar to findings from a previous study (38). Preincubation of the same human milk sample (1:2) with HIV-1 before addition to CD4 + T lymphocytes ( Figure 1B) showed no inhibitory effect in comparison to the PBS control, indicating that the inhibition shown in Figure 1A is not due to a direct virucidal effect of the milk and that the effect is likely conferred on the CD4 + lymphocyte.…”
Section: The Effect Of Human Milk On Direct Hiv-1 Infection Of Cd4 + supporting
confidence: 81%
“…Macrophages in human milk are found at varying concentrations during lactation (34) and are preferentially infected with viruses that utilize the CCR5 coreceptor for viral entry (R5) and that are typically associated with HIV-1 transmission (35,36). Mammary epithelial cells are present in human milk, and these cells are predominantly infected with viruses utilizing the CXCR4 coreceptor (X4), virus strains that seldom undergo transmission (37,38). CD4 + T lymphocytes are also present in human milk, and these cells can be infected with both R5 and X4 strains, depending on the cellular phenotype and cell activation status (39,40).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to macrophages and lymphocytes, mammary epithelial cells are thought to be the sources of HIV-1 in breast milk. Interestingly, the susceptibility of those cells to HIV-1 strains differs: macrophages support replication of R5-tropic HIV-1 much better than that of X4-tropic HIV-1, lymphocytes support replication of R5-and X4-tropic HIV-1 equally well, and mammary epithelial cells support replication of X4-tropic rather than R5-tropic HIV-1 (18,28,30). It is, however, unclear which cell type plays a major role in mother-to-child transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are susceptible to R5-tropic HIV-1 but much less to X4-tropic virus (1, 3) which utilizes CXCR4 as an entry coreceptor. Although the major source of HIV-1 in mature (Ͼ2 weeks after delivery) milk remains unknown, mammary epithelial cells, the predominant cell type in mature milk (8), have been shown to be susceptible to certain (mostly X4-tropic) HIV-1 strains (18,28,30).…”
mentioning
confidence: 99%
“…Further studies have also shown that vaginal secretions contain cathepsin D and exposure of lymphocyte cultures to these secretions increased HIV-1 replication in these cells [45] . Furthermore, human breast milk also enhanced HIV-1 infection of lymphocyte cultures which was inhibited by anti-cathepsin D antibodies or pepstatin A, an inhibitor of cathespin D suggesting that cathepsin D may interact with gp120 to modify the affinity of HIV-1 co-receptors thereby enhancing HIV-1 infectivity [45,46] . The current study demonstrates for the first time that heroin enhances the expression of the preprotein form of cathepsin D in NHA.…”
Section: Discussionmentioning
confidence: 99%